Determination of Endophytic Fungi as Induce Resistance Agent of Chilli Pepper Against Pepper Yellow Leaf Curl Disease - Lestari, Susanti Mugi; Hidayat, Sri Hendrastuti; Widodo, Widodo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Pepper yellow leaf curl disease caused by Pepper yellow leaf curl virus becomes a major problem on chilli pepper in Indonesia since 2000. Endophytic fungi has the potency to suppress plant diseases by acting as induced resistant agent. The objective of this research was to determine the effect of endophytic fungi application on incidence of yellow leaf curl disease of chilli pepper. Four isolates of endophytic fungi, i.e. Cercospora nicotianae isolate H5, Curvularia sp. isolate H12, Fusarium sp. isolate AC-2.7 and AC-4.5 were applied as seed treatment and leaf spray on 2 chilli varieties, ‘Biola’ and ‘Luwes’. Observations of incubation period showed that delayed symptom occurred on application of Fusarium sp. isolate AC-2.7 and Curvularia sp. isolate H12. Disease incidence reached 100 % in all treatments. Less severe symptom was observed on application of Curvularia sp. isolate H12. Most plants infected by PYLCIV showed obvious symptoms of yellow mosaic, leaf curling and stunting. Plant productivity analysis showed that application of Fusarium sp. isolate AC-2.7 resulted higher fruit weight and this treatment may induce tolerant response of the plants to PYLCIV infection. Initial effort to evaluate endophytic fungi as biocontrol agents for pepper yellow leaf curl disease should be studied further.